2014
DOI: 10.1007/s13770-014-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet rich plasma combined with microfracture for the treatment of chondral defect in a rabbit knee

Abstract: Recently, many clinical studies have been published regarding platelet-rich plasma (PRP) injection for early degenerative joint disease. We evaluated the cartilage repair potential of platelet-rich plasma when injected into the knee joint. Articular, cartilage defects 4 mm in diameter and circular in shape were made in the trochlear region of 20 knees in 10 New Zealand white rabbits who were divided into two groups. The left knees in the control group underwent microfracture, and the right knees in the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Huh et al demonstrated that microfracture following PRP injection resulted in repaired cartilage that was more histologically differentiated than that from microfracture alone. 10 These findings coincide with those reported previously, in which microfracture was tested as a treatment option. 11-13…”
Section: Discussionsupporting
confidence: 91%
“…Huh et al demonstrated that microfracture following PRP injection resulted in repaired cartilage that was more histologically differentiated than that from microfracture alone. 10 These findings coincide with those reported previously, in which microfracture was tested as a treatment option. 11-13…”
Section: Discussionsupporting
confidence: 91%
“…Under our experimental conditions, however, treatment with BMP-12 was unlikely to be effective on tenogenic differentiation of TMSCs; it increased mRNA of only COL1, but not of TNMD and SCX (data not shown). Some of chondrogenic differentiation factors such as platelet rich plasma [39] and growth differentiation factor-5 [40] are also likely to mediate tenocytic differentiation because both chondrogenesis and tenogenesis are highly active and cooperative in particular during musculoskeletal tissue regeneration. However, whether these chondrogenic differentiation factors indeed mediate tenogenic differentiation of TMSCs warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that several PRP preparations have been described in the scientific literature, which have very similar cell concentrations to the PRP preparations evaluated in this study. In this sense, we could classify these substances as transitional PRP because Different rabbit PRP preparations have been evaluated in diverse disease models (29,31,39,40). However, information related to the standard PRP processing protocols and growth factor concentrations is not usually found in these studies (29,31,40).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we could classify these substances as transitional PRP because Different rabbit PRP preparations have been evaluated in diverse disease models (29,31,39,40). However, information related to the standard PRP processing protocols and growth factor concentrations is not usually found in these studies (29,31,40). Thus, it is important to stress that a standard PRP processing protocol must include information such as the type of anticoagulant tubes or preparation kits, the relative centrifugation forces, the duration of centrifugation, the number of centrifugation steps, the activating substances employed, cell counts, growth factor concentrations, and platelet-related activation parameters, such as mean platelet volume and platelet distribution width (14,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation